THE INFLUENCE OF ONLINE PROMOTION THROUGH CELEBRITY ENDORSEMENT ON CONSUMER BUYING INTEREST - Desven Sulaiman; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
Online promotion is a promotional activity carried out to introduce and inform consumers about a product through the internet media which is carried out through social media such as Instagram, Facebook, Twitter and so on. Celebrity Endorsement is one of the supporting media used to promote a product, celebrities are influencers who are better known on Instagram who have many followers. The purpose of this study is to determine the effect of online promotion and celebrity endorsement on consumer buying interest. This research method uses a data collection method where the collected data is drawn into a conclusion and produces a hypothesis. This study provides a literature review on the effect of online promotion and celebrity endorsement on consumer buying interest. This conceptual framework can help businesspeople if they want to create an online promotion strategy by using celebrities in marketing their products. This study provides an idea for businesspeople to market their products with celebrity endorsement services or celebrities, because both influence consumer buying interest which will increase sales of the product. This will provide 2 benefits, namely for the party doing the promotion and for the company. From this study, there is a positive and significant influence between online promotion and celebrity endorsement on consumer buying interest.